On Determining the Status of the Units “Verb + Postverb” in English - Клиюнайте, Ина (Kalbotyra, 1987)
In the present article an attempt is made to determine the status of the English units “verb + out (up, on, etc.)” (e. g. to take off, to eat out, to bring up, to go out, etc.). We are of the opinion that these units should be classified into: 1) free word combinations “verb + adverb”, cf. to live out, to sleep out, 2) analytical word, to set up, to cut out with a second element as a derivative morpheme; 3) intermediate cases between analytical words and units “verb + adverb”, i. e. verbs of motion where the second element indicates direction, e. g. to go out, to come up (to sb), 4) phraseological units, e. g. to bring up, to take in, etc.